Global biogeography of warning coloration in the butterfly Danaus chrysippus. (1st June 2022) - Liu, Wanzhen; Smith, David A. S.; Raina, Gayatri; Stanforth, Rowan; Ng'Iru, Ivy; Ireri, Piera; Martins, Dino J.; Gordon, Ian J.; Martin, Simon H.
Abstract : Warning coloration provides a textbook example of natural selection, but the frequent observation of polymorphism in aposematic species presents an evolutionary puzzle. We investigated biogeography and polymorphism of warning patterns in the widespread butterfly Danaus chrysippus using records from citizen science ( n = 5467), museums ( n = 8864) and fieldwork ( n = 2586). We find that polymorphism in three traits controlled by known mendelian loci is extensive. Broad allele frequency clines, hundreds of kilometres wide, suggest a balance between long-range dispersal and predation of unfamiliar morphs. Mismatched clines for the white hindwing and forewing tip in East Africa are consistent with a previous finding that the black wingtip allele has spread recently in the region through hitchhiking with a heritable endosymbiont. Light/dark background coloration shows more extensive polymorphism. The darker genotype is more common in cooler regions, possibly reflecting a trade-off between thermoregulation and predator warning. Overall, our findings show how studying local adaptation at the global scale provides a more complete picture of the evolutionary forces involved.